Assessing the Impact of Monensin Sodium on Early Lactating Buffalo: An In-Depth Analysis of Dry Matter Consumption and Milk Characteristics - Rakesh Kumar Yadav, Apoorva Narad, Kamalraj R (Revista Electronica de Veterinaria, 2024)
This study illuminates the nutritional dynamics of lactating buffalos by investigating the relationship between Milk characteristics and Dry Matter Intake (DMI). Determine effect of monensin sodium ingestion on earlier lactation buffaloes by an analysis of DMI with milk quality. Thirty apparent health buffaloes in the second week of lactation were chosen, and they were divided into two equal categories, the studycategory and the control category. The studycategorycomplemented the regular ration with monensin sodium at a dosage of 400 mg/day until the 12th week of lactation, whereas the control category was fed the standard ration consisting of concentrate, green fodder, and dry fodder. During the period of the examination, weekly records of the DMI, milk production, and milk components were kept. The control category had approximately 2.90% drop in DMI, with theimportance (p<0.05) variance in DMI of 10.32±0.02 and 10.03±0.06, respectively, compared to the studycategory. Buffaloes given monensin complementation had an average milk production (kg/d) of 7.18±0.11 and 7.77±0.25. When compared to the control category, buffaloes given monensin complements displayed a decreased fat percentage.